2012
DOI: 10.1124/mol.112.081844
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 Post-transcriptionally Regulates the Expression and Function of P-glycoprotein in Intestinal Epithelial Cells

Abstract: P-glycoprotein (P-gp/MDR1) is a multispecific efflux transporter regulating the pharmacokinetics of various drugs. Although P-gp expression in the small intestine is elevated after liver ischemiareperfusion (I/R) injury, the regulatory mechanism remains to be clarified. MicroRNAs (miRNAs) play an important role in the posttranscriptional regulation of the expression of drug transporters. Here, we investigated the intestinal expression profile of miRNAs after liver I/R and the role of miRNAs in the post-transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…According to several recent studies, miRNAs modulate MDR by altering the expression of ABC transporters, such as BCRP and P-gp, in tumor cells (Haenisch et al, 2014). For example, miR-129 and miR-145 inhibit P-gp expression and sensitize human cancer cells to chemotherapy drugs by directly targeting the 3′-UTR of MDR1 (Ikemura et al, 2013; Lu et al, 2017). Additionally, the overexpression of miR-506 and miR-138 have been reported to indirectly downregulate P-gp expression by regulating different signaling pathways (Requenez-Contreras et al, 2017; Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to several recent studies, miRNAs modulate MDR by altering the expression of ABC transporters, such as BCRP and P-gp, in tumor cells (Haenisch et al, 2014). For example, miR-129 and miR-145 inhibit P-gp expression and sensitize human cancer cells to chemotherapy drugs by directly targeting the 3′-UTR of MDR1 (Ikemura et al, 2013; Lu et al, 2017). Additionally, the overexpression of miR-506 and miR-138 have been reported to indirectly downregulate P-gp expression by regulating different signaling pathways (Requenez-Contreras et al, 2017; Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…36,37 MDR1 is also regulated at RNA level by micro RNAs (miR) such as miR-145, miR-27a and miR-331-5p that bind directly the 3ʹUTR of ABCB1 mRNA to decrease MDR1 expression. 38,39 Some other miR (miR-137) indirectly decrease MDR1 expression by targeting the YB-1 transcription factor that upregulates MDR1 expression by fixation on ABCB1 promoter. 40,41 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, overexpression of miR-451 (Kovalchuk et al, 2008), miR-145 (Ikemura et al, 2013), miR-298 (Bao et al, 2012) and miR-27a (Zhao et al, 2011;Zhang et al, 2010) are found to inhibit the MDR1 gene expression, but miR-331-5p (Feng et al, 2011) increase MDR1 expression by direct interaction with the 3 0 -UTR of the MDR1 mRNA region. Several miRs have been described as DOI: 10.3109/03602532.2015.1007012 Role of MDR1 in pharmacokinetic changes under hypoxia 5 Drug Metabolism Reviews Downloaded from informahealthcare.com by University of Calgary on 02/03/15 ''possibly indirect regulators'' of MDR1, for instance, miR-451, miR-27a, miR-21 (Seca et al, 2013), miR-130a (Yang et al, 2012) and miR-let-7 (Boyerinas et al, 2012), by targeting other mRNAs, which code for intermediate proteins or transcription factors involved in MDR1 gene activation ( Figure 5).…”
Section: Mirnas As Regulators Of Mdr1 Gene Expression Under Hypoxiamentioning
confidence: 98%